LEADERSHIP, DISCIPLINE AND MOTIVATION AFFECTING TO THE PERFORMANCE - Marsuhin Marsuhin; Suwignyo Widagdo; Murtadlo Murtadlo (MBA - Journal of Management and Business Aplication, 2018)
This study aims to identify and analyze the influence of leadership, discipline and motivation on the performance, as well as to find out which of the leadership, discipline and motivation are the dominant influence on performance. The subjects in this study are members of Lumajang Police Force Sabhara totaling 63 people.This research uses explanatory research. As independent variables, namely leadership, discipline and motivation, and the dependent variable is the performance. Analysis of the data used are validity and reliability, the classic assumption test, regression analysis, and hypothesis testing.The results showed that the leadership has a significant effect on performance, discipline significant effect on performance, motivation significant effect on the performance and motivation of the dominant influence on performance. The coefficient of determination (R2) is equal to 0,795. This means that 79.50% of performance can be explained by the leadership, discipline and motivation. While the rest of 20,50% performance is influenced by other variables not examined in this study.